Environmental and Socio-Economic Determinants of Life Expectancy: Empirical Evidence from Indonesia - Ika Pramita; Kukuh Arisetyawan (Universitas Kadiri, 2025)
The objective of this research is to evaluate the influence of several key socioeconomic and public health factors namely, access to clean water and sanitation, the open unemployment rate, education levels, and per capita health expenditure on Life Expectancy in Indonesia. Utilizing panel data from all 34 provinces over the period 2020–2023, the analysis employs a panel regression methodology. The most appropriate model was selected through the Chow Test and Hausman Test, which indicated the Fixed Effects Model (FEM) as the most robust estimator. The findings reveal that access to clean water, access to sanitation, and education have a positive and statistically significant effect on life expectancy. Conversely, the open unemployment rate exerts a significant negative influence. Education emerged as the most dominant variable, with each additional year of mean schooling associated with an increase in life expectancy of 1.41 years. However, per capita health expenditure was not found to have a statistically significant impact. In conclusion, this study affirms that enhancing life expectancy requires an integrated policy approach. This includes improvements in basic infrastructure (water and sanitation), the expansion of educational access, and a reduction in unemployment rates to foster the socio-economic stability that underpins population health.